Global burden of esophagus cancer, stomach cancer and colon and rectal cancer from 1990 to 2050 - Rao Wang; Wei-Guang Liu (Medicine, 2026)
Esophageal cancer, stomach cancer, and colon and rectal cancer (CRC), as the main components of gastrointestinal tract cancer (GTC), represent significant obstacles to reducing the global cancer burden. Therefore, obtaining an epidemiological characteristic of the 3 major GTCs is highly important. This study aims to analyze and forecast the changing trends in the burden of the 3 major GTCs, offering a certain theoretical foundation for cancer public health policymakers. The data utilized in this study were all sourced from the Global Burden of Disease study 2021. Specifically, the case numbers and age-standardized rate (ASR) for prevalence, death, and disability-adjusted life years of esophageal cancer, stomach cancer, and CRC were included. Additionally, the estimated annual percentage change of the 3 major GTCs was computed for the period spanning from 1990 to 2021 across 5 distinct socio-demographic index and 21 Global Burden of Disease regions. Moreover, a Bayesian age-period-cohort model was constructed to project the disease burden of the 3 major GTCs from 2022 to 2050. From 1990 to 2021, the number of cases of the 3 major GTCs showed an overall increasing trend. Regarding ASRs, with the exception of the increasing age-standardized prevalence rate of CRC, the ASRs of the remaining GTCs demonstrated a downward trend. The disease burden of the 3 GTCs was higher among males compared to females, predominantly affecting individuals aged 50 and above. The regions with notable ASRs of the 3 major GTCs were East Asia and high-income Asia. The prediction outcomes also suggested that, apart from the age-standardized prevalence rate of CRC, the burden of the 3 major GTCs might display a decreasing trend in the next 29 years. Although the ASRs of the 3 primary types of GTC exhibit a downward trend, the case counts of these types still maintain a relatively high baseline level. Consequently, conducting GTC screening in specific regions, developing relevant health policies and popularizing disease-related knowledge continue to hold critical significance.